2016
DOI: 10.1117/1.jbo.21.12.126011
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence confocal endomicroscopy of the cervix: pilot study on the potential and limitations for clinical implementation

Abstract: Abstract. Current diagnostic capabilities and limitations of fluorescence endomicroscopy in the cervix are assessed by qualitative and quantitative image analysis. Four cervical tissue types are investigated: normal columnar epithelium, normal and precancerous squamous epithelium, and stromal tissue. This study focuses on the perceived variability within and the subtle differences between the four tissue groups in the context of endomicroscopic in vivo pathology. Conclusions are drawn on the general ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…J Tan et al reported that the sensitivity for detection of CIN was 97%. However, low inter-observer agreement reported by Schlosser C et al is problematic for a clinical setting [17,18]. Endocytoscopy provides sharp images that re ect the size, chromatin concentration and density of the nucleus similar to histopathology, and it enables diagnosis of CIN in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…J Tan et al reported that the sensitivity for detection of CIN was 97%. However, low inter-observer agreement reported by Schlosser C et al is problematic for a clinical setting [17,18]. Endocytoscopy provides sharp images that re ect the size, chromatin concentration and density of the nucleus similar to histopathology, and it enables diagnosis of CIN in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The limited permeation of the dye into the surface 2 to 3 cell layers (i.e., ≈30 μm) limits FE contrast to the tissue surface. 11 While very strong and prolonged illumination of stained cells may cause cellular photo damage, 16 AH has a reported long history of safe clinical usage as an antiseptic compound. AH molecules fluoresce with a spectrum centered at about λ ¼ 500 nm.…”
Section: Device and Imaging Approachmentioning
confidence: 99%
“…Owing to the same imaging field of view for both modalities, the separation between severe dysplasia and all other data points is achieved with very high certainty, as nuclear density serves as an established imaging feature to confirm severely dysplastic lesions. 11 This removes some of the localization uncertainty often encountered for other imaging devices when coregistering images to histopathology.…”
Section: Quantitative Dual-mode Endomicroscopy Data Analysismentioning
confidence: 99%
See 2 more Smart Citations